Busting myths: Conceptual approach to the sexuality of people with functional diversity - Martinez-Martinez, Antonio Luis; Bote, Marcos (IJRDO - Journal of Social Science and Humanities Research, 2017)
Background: Sexuality is one the most transcendental aspects of human nature. We are all born sexual and therefore we have the right to experience it, but in the particular case of people with functional diversity the situation is complex, they have been denied for many centuries the pleasure of it, considering them as individuals lacking in attraction and as asexual beings. Objective/Hypothesis. The purpose of this article is to carry out a conceptual approach to the sexuality of people with functional diversity, analyzing its most relevant dimensions. Methods: First, we will develop the meaning of sexuality and the importance given to it, since the perspective of disability according to several authors. Later erotic desires and fantasies will be explained, focusing on the main sexual myths and misconceptions regarding this group. Third, we will discuss how they live their own sexuality. Finally, we will discuss the role of the sexual assistant, addressing the most significant aspects of sexual assistance. Results: The sexuality of people with disability remains as a residual topic in academic research. Perceptions of this issue by society is anchorage in myth describing this indidviudals as asexual of uncapable of having sexual desires or relations. The sexual assistance reamins under controversy and underregulated in most countries Conclussions: Further research must be conducted in order to raise awareness about the issue, either in the academia, the society and the legislators